Studies on photoyellowing of silk fibroin and alteration of its tyrosine content. Issue 4 (2nd April 2016) - Wang, Zongqian; Chen, Weiguo; Cui, Zhihua; He, Kaijun; Yu, Wei
Abstract : The photoyellowing progress of silk fibroin and its influence factors under ultraviolet irradiation have been studied, which was conducted by combining different ultraviolet wavelengths, different ultraviolet irradiancies, and different irradiation times. The blue-ray whiteness after ultraviolet irradiation was tested to characterize the course of photoyellowing of silk fibroin. The result shows that the photoyellowing degree of silk fibroin varies significantly under ultraviolet irradiation of different wavelengths and with the increasing in ultraviolet irradiancy at 313-nm wavelength, the photoyellowing degree aggravates correspondingly, while the ultraviolet irradiancy at 340-nm wavelength has little obvious impact. Additionally, the photoyellowing degree of silk fibroin is positively correlated to ultraviolet irradiancy and irradiation time. To quantitatively analyze the alteration of tyrosine content during the photoyellowing of the silk fibroin, l -tyrosine standard curve Y  = 8.14666 X  − 0.88951 was established using HPLC with linear coefficient r  = 0.99991 and precision degree coefficient of tyrosine analyses RSD1  = 0.21%. Meanwhile, the tyrosine content of silk fibroin after acid hydrolysis was quantitatively analyzed by HPLC with precision degree coefficient RSD2  = 1.12%. It can be seen that the change rate of the blue-ray whiteness of silk fibroin is positively proportional to the photodegradation rate of tyrosine, but the photodegradation rate of tyrosine ingredient is lower than the change rate of the blue-ray whiteness of silk fibroin.